The Application of Irap Markers in the Breeding of Papaya (Carica Papaya L.) - Rashid, K.; Othman, R.Y.; Ali, B.S.K.S.; Mohd-Yusuf, Y.; Nezhadahmadi, A. (Indian Society for Education and Environment, 2014)
Papaya is an important medicinal crop which is used in industries and other healthcare products. This study was conducted to facilitate the selection of Papaya Ring Spot Virus (PRSV) resistant papayas in breeding programs by DNA fingerprinting method. By using Inter-Retrotransposons Amplified Polymorphism molecular markers, 5 out of 45 possible primer combinations (28 IRAP primers combination and RT primers) showed significant polymorphism in DNA banding patterns that determined parental-progeny relations and classified progenies based on their resistance towards PRSV. Primers combination of LTR 6149 and LTR 6149 had the highest degree of polymorphism which was 75% of polymorphic bands. It is observed that only 1 out of 5 combinations of primers demonstrated DNA banding patterns similar to the previous study by Malaysian Agriculture and Research Development Institute (MARDI). Phylogenetic trees were constructed to detect the relation of papaya samples, and those which based on primers combination of LTR 6150 and Nikita showed resistant progenies with resistant parent. Furthermore, progenies from L90 were found to be closely related to the parent Tainung (T5) whilst progenies from L13 and L33 were closely related to another parent, Eksotika (E6). L90 with symptom-free fruits was the most tolerant followed by L33 and L13. So, the best primers in terms of inheritance pattern based on the PRSV resistance trait (LTR 6150 and Nikita primers) were suggested to be further applied in Molecular Assisted Breeding (MAB) or Molecular Assisted Selection (MAS) for papaya breeding programs.